PENGARUH ROA, LEVERAGE, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PERTAMBANGAN ERA JOKOWI – JK - Gumono, Clarissa Octa (Media Akuntansi dan Perpajakan Indonesia, 2021)
Taxes are income for the state which are useful for financing state activities and operations. Unfortunately, taxes are not profitable for companies. Taxes can decrease its profit. This situation triggers the company to take action related to agency theory. This actions taken by managing tax financing so that it can be effective and efficient without violating existing regulations. That actions called tax avoidance. Tax avoidance takes advantages of the grey area in the tax regulations so that the actions taken legally. Tax avoidance in this study is used as the dependent variable by calculating the cash effective tax rate (cash ETR). Independent variable in this study are return on assets (ROA), leverage, and capital intensity. The existence of these variables are used to support the purpose of this study. The purpose of this study is to determine the influence of ROA, Leverage and Capital intensity on tax avoidance. The data used are from the financial reports and annual reports of mining sector companies listed in Indonesia Stock Exchange during the Jokowi - JK’s era.